Knowledge and Attitude towards Ebola Virus Disease among Secondary School Students in Abakaliki, South-east, Nigeria - E. U. Nwonwu; C. Alo; A. F. Una; U. C. Madubueze; N. C. Eze; C. O. Mbachu (Archives of Current Research International, 2017)
Introduction: Ebola virus disease (EVD) is an acute haemorrhagic fever. It is also a zoonotic disease which has posed a serious public health problem in the West African Sub-Region. The study was conducted to determine the level of knowledge and attitude towards EVD among Secondary School Students in Abakaliki, Ebonyi State, Nigeria. Methods: A cross-sectional descriptive study was carried out among 318 secondary school students in Abakaliki, Ebonyi State, selected through multistage sampling method. Information and permission were obtained from the State Ministry of Education, Informed consent from the principals of the schools and their class teachers. Assent was obtained from selected students prior to the study. Data was collected with pre-tested semi-structured questionnaires and analyzed using statistical package for the social science (SPSS) version 20. Results were treated with strict confidentiality. Results: Majority of the respondents (85.5%) were between 15 to 19 years. Students in SSS 2 constituted the greatest proportion of respondents, 57.0% and 48.8% for public and private schools respectively. One hundred percent of the respondents had heard about EVD. Knowledge of EVD was generally poor for majority of the students in both schools, the proportion being higher in the public (65.8%), compared to the private schools (40.6%). Greater proportion (70.6%) of those in private schools had positive attitude to EVD compared to 53.8% in public schools. Conclusion: Respondents from private schools were more knowledgeable and exhibited more positive attitude than respondents from public schools. Recommendation: Sensitisation and health education of secondary school students on EVD.